Pengaruh Digital Marketing, Influencer Marketing Dan Ewom, Terhadap Keputusan Pembelian Viva Cosmetic di Kota Bat - Lestari, Rosa; Pitri Nainggolan, Nora (Masyarakat Ekonomi Syariah Bogor, 2024)
This research investigates how digital marketing, influencer marketing, and ewom influence consumers' decisions to buy Viva Cosmetic in the city of Batam. The population of this study is the Sagulung community in Batam city who use Viva Cosmetic in 2024, but their number is unknown. The number of samples collected using the Jacob Cohen formula reached 204 people who were chosen deliberately. Data quality testing, classical assumption testing, and hypothesis testing are several steps in the data analysis process. The results of multiple linear aggression analysis show that digital marketing influences purchasing decisions by 34.2%. Influencer marketing influences 35.1% of purchasing decisions, and Ewom influences 35.6%. According to coefficient of determination (R2) analysis, digital marketing, influencer marketing, and eWOM can be responsible for 57.6% of the variation in purchasing decisions. The t test and f test show that EWOM, influencer marketing, and digital marketing have a positive and significant influence, both partially and simultaneously, on consumers' decisions to buy Viva cosmetic products in Batam